71 questions linked to/from How to show that L = L(G)?
2k views

### Proving that a word is *not* generated by a context-free grammar

I saw the answer in one of the solutions and I cannot figure out how they got the answer. The question is asked if the word is in the language or not for CNF... How did they get the answer so that ab ...
2k views

### Why is the distinction between linear and context-free grammars useful?

The linear grammar is a grammar that's either left, right or left and right linear. The context-free grammar can contain any kind of productions of non-terminals and terminals. All linear grammars ...
5k views

### Prove correctness of DFA ending with ab

I have the following deterministic finite automaton and I am need to prove correctness of the claim that this automata accepts $\{wab \mid w\in \{a,b\}^*\}$ I know that I need to prove by induction ...
4k views

### Equivalence of two context free grammars [for the given example]

I know that in general it is undecidable whether two context free grammars generate the same language, but I have to do this exercise and I am finding myself somewhat stuck: G1: S->e|aB|bA B->bS|...
3k views

### Why is the language of even-length non-palindromes context-free?

We know $L_1=\{w_1 w_2 \in (a+b)^*\mid |w_1|=|w_2|, w_2 \neq w_1^{\;\mathrm{R}}\}$ is a context-free language. Can anyone help me produce a PDA or give me any hint how I can quickly understand why ...
3k views

### PDA or CFG for language $L= \{a^ib^j | 2i \leq 2j \leq 3i, i>0\}$

Can someone help with this $L= \{a^ib^j | 2i \leq 2j \leq 3i, i>0\}$
4k views

556 views

### Proof for BFS and DFS equivalence

I'm trying to prove (by induction) that BFS in equivalent to DFS, in the sense that they return the same set of visited nodes, but I'm stuck in the middle of some of the cases. Let $G$ be a directed ...
Say you are given the following CFG $G$: $$S \to S_1 \mid S_2 \\ S_1 \to AbAS_1c \mid \epsilon \\ S_2 \to BaBS_2c \mid \epsilon \\ A \to Aa \mid \epsilon \\ B \to Bb \mid \epsilon$$ What is $L(G)$? ...
### Regular expression $(a^{*}b^{*})^{*} = \left( a+b \right)^{*}$ proof
Im having a lot of trouble proving that for the Regular expression $R_{1} = \left( a^{*} b^{*} \right)^{*}$ and $R_{2} = \left( a+b \right)^{*}$ that $L \left( R_{1} \right) = L \left( R_{2} \right)$. ...